Effects of stereotactic aspiration on brainstem hemorrhage in a case series - Du, Lei; Wang, Ji-Wei; Li, Cong-Hui; Gao, Bu-Lang (Frontiers in Surgery, 2022)
Purpose: Brainstem hemorrhage is usually treated conservatively with medication and has a high mortality and morbidity. Stereotactic aspiration can directly microinvasively draw out the hemorrhage within a narrow space in the brainstem, thus promoting quick recovery and potentially saving the life of the patient. This study was to investigate the effect of stereotactic aspiration on patients with brainstem hemorrhage in a case series. Materials and methods: Forty-two patients with brainstem hemorrhage were enrolled for stereotactic aspiration of the brain hemorrhage, and another 30 patients with brainstem hemorrhage were enrolled for conservative treatment. The clinical and imaging data were analyzed and compared. Results: Stereotactic aspiration was successful in all patients (100%) with immediate elimination of hematoma in the brainstem. In five patients with the hemorrhage extending to the fourth ventricle (n=1) and basal ganglia (n=4), the hemorrhage was eliminated, resulting in good outcomes. Four patients died of multiple organ failure after aspiration, resulting in a mortality rate of 9.5%. One week after surgery, the GCS score ranged 3-11 (mean 5.9±2.3). At one-month follow-up, two patients were lost, additional two patients died, and 36 patients were alive, with the GCS score ranged 3-15 (mean 8.6±2.1), significantly (P<0.01) greater than before surgery. The mRS score was 5 before treatment, 5 (4.4, 6) at one week after surgery, and 5 (4, 6) at one month. In the conservative group, 16 (53.3%) patients died during hospitalization. The GCS score was 0-6 (mean 2.3±1.1), significantly (P<0.05) worse than at admission or that in the aspiration group at one month. The mRS score at one month was 6 (5, 6), significantly (P<0.05) worse than that in the aspiration group. Conclusion: Stereotactic aspiration for brainstem hemorrhage as an approach of microinvasiveness may be effective in evacuating brainstem hemorrhage and promote quick recovery of the patient, resulting in better clinical outcomes.